Photophysics of BODIPY-Based Photosensitizer for Photodynamic Therapy: Surface Hopping and Classical Molecular Dynamics - Pederzoli, Marek; Wasif Baig, Mirza; Kývala, Mojmír; Pittner, Jiří; Cwiklik, Lukasz (Journal of chemical theory and computation, 2019)
Halogenated BODIPY derivatives are emerging as important candidates for photodynamic therapy of cancer cells due to their high triplet quantum yield. We probed fundamental photophysical properties and interactions with biological environments of such photosensitizers. To this end, we employed static TD-DFT quantum chemical calculations as well as TD-DFT surface hopping molecular dynamics on potential energy surfaces resulting from the eigenstates of the total electronic Hamiltonian including the spin-orbit (SO) coupling. Matrix elements of an effective one-electron spin-orbit Hamiltonian between singlet and triplet configuration interaction singles (CIS) auxiliary wave functions are calculated using a new code capable of dealing with singlets and both restricted and unrestricted triplets built up from up to three different and independent sets of (singlet, alpha, and beta) molecular orbitals. The interaction with a biological environment was addressed by using classical molecular dynamics (MD) in a scheme that implicitly accounts for electronically excited states. For the surface hopping trajectories, an accelerated MD approach was used, in which the SO couplings are scaled up, to make the calculations computationally feasible, and the lifetimes are extrapolated back to unscaled SO couplings. The lifetime of the first excited singlet state estimated by semiclassical surface hopping simulations is 139 ± 75 ps. Classical MD demonstrates that halogenated BODIPY in the ground state, in contrast to the unsubstituted one, is stable in the headgroup region of minimalistic cell membrane models, and while in the triplet state, the molecule relocates to the membrane interior ready for further steps of photodynamic therapy.
Keywords: Photosensitizing Agents; Boron Compounds; sloučeniny boru; Photochemical Processes; Photochemotherapy; simulace molekulární dynamiky; fotosenzibilizující látky; Quantum Theory; teorie funkcionálu hustoty; povrchové vlastnosti; fotochemoterapie; Density Functional Theory; Molecular Dynamics Simulation; kvantová teorie; Surface Properties; fotochemické procesy